Repressed, remitted, rejected : German reparations debts to Poland and Greece - Roth, Karl Heinz; Rübner, Hartmut (2022)
Zusammenfassung: "Since unification, the Federal Republic of Germany has carried out vaunted efforts to make amends for the crimes of the Third Reich. Yet it remains the case that the demands for restitution by many countries that were occupied during the Second World War are unresolved, and recent demands from Greece and Poland have only reignited old debates. This book reconstructs the German occupation of Poland and Greece and gives a thorough accounting of these debates. Working from the perspective of international law, it deepens the scholarly discourse around the issue, clarifying the 'never-ending story' of German reparations policy and making a principled call for further action"